2022
DOI: 10.26745/ahbvuibfd.1110109
|View full text |Cite
|
Sign up to set email alerts
|

Hedge and Safe Haven Properties of Gold and Cryptocurrencies for the BİST100 Index: The Covid-19 Pandemic Effects

Abstract: After the Covid-19 outbreak, economic turmoil and severe market crashes have been observed around the world. During this crisis period, cyriptocurrencies and gold have become potentially good hedge and/or safe haven assets for especially the stock investors in emerging markets. This study investigates whether or not Bitcoin, Etherium, Ripple, Litecoin and gold markets have hedge and/or safe-haven properties for Borsa İstanbul through a regression system modeled under the assumption of GARCH(1,1) error terms. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…(2022) çalışmalarında Bitcoin ile BIST 100 arasında bir ilişkinin bulunmadığına dair sonuçlar raporlamışlardır. Serttaş (2022) ise Bitcoin'in BIST 100'e karşın COVID-19 öncesi zayıf riski dengeleme özelliği gösterdiğini bulgulamıştır.…”
Section: Literatürunclassified
See 1 more Smart Citation
“…(2022) çalışmalarında Bitcoin ile BIST 100 arasında bir ilişkinin bulunmadığına dair sonuçlar raporlamışlardır. Serttaş (2022) ise Bitcoin'in BIST 100'e karşın COVID-19 öncesi zayıf riski dengeleme özelliği gösterdiğini bulgulamıştır.…”
Section: Literatürunclassified
“…Dirican and Canoz (2017), Gürsoy and Tunçel (2020), Gürsoy (2020), Tunçel et al (2022) found no significant relationship between Bitcoin and BIST 100. However, Serttaş (2022) discovered that Bitcoin exhibited a weak hedging feature against BIST 100 before the COVID-19 period. In the international literature, some studies have found evidence that Bitcoin provides hedging capabilities against stock markets (Dyhberg, 2016;Bouri et al, 2017a;Bouri et al, 2017b;Chan et al, 2019;Stensas et al, 2019).…”
Section: Research Subject and Purposementioning
confidence: 99%